SARS-CoV-2 spike protein induces the cytokine release syndrome by stimulating T cells to produce more IL-2 - Niu, Chao; Liang, Tingting; Chen, Yongchong; Zhu, Shan; Zhou, Lei; Chen, Naifei; Qian, Lei; Wang, Yufeng; Li, Min; Zhou, Xin; Cui, Jiuwei (Frontiers in Immunology, 2024)
Introduction Cytokine release syndrome (CRS) is one of the leading causes of mortality in patients with COVID-19 caused by the SARS-CoV-2 coronavirus. However, the mechanism of CRS induced by SARS-CoV-2 is vague. Methods Using spike protein combined with IL-2, IFN-γ, and TNF-α to stimulate human peripheral blood mononuclear cells (PBMCs) to secrete CRS-related cytokines, the content of cytokines in the supernatant was detected, and the effects of NK, T, and monocytes were analyzed. Results This study shows that dendritic cells loaded with spike protein of SARS-CoV-2 stimulate T cells to release much more interleukin-2 (IL-2,) which subsequently cooperates with spike protein to facilitate PBMCs to release IL-1β, IL-6, and IL-8. These effects are achieved via IL-2 stimulation of NK cells to release tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ), as well as T cells to release IFN-γ Mechanistically, IFN-γ and TNF-α enhance the transcription of CD40, and the interaction of CD40 and its ligand stabilizes the membrane expression of toll-like receptor 4 (TLR4) that serves as a receptor of spike protein on the surface of monocytes. As a result, there is a constant interaction between spike protein and TLR4, leading to continuous activation of nuclear factor-κ-gene binding (NF-κB). Furthermore, TNF-α also activates NF-κB signaling in monocytes, which further cooperates with IFN-γ and spike protein to modulate NF-κB–dependent transcription of CRS-related inflammatory cytokines. Discussion Targeting TNF-α/IFN-γ in combination with TLR4 may represent a promising therapeutic approach for alleviating CRS in individuals with COVID-19.